Artificial Intelligence Applications That Support: Business Organizations and EGovernment in Administrative Decision - Mohammad Ali Alqudah; Leyla Muradkhanli; Mohammad Al-Awasa (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
There are various generations of decision support systems related to the field of artificial intelligence, and this research paper deals with studying and analyzing the most important applications, tools, and techniques thereof in modern business organizations and e-government. Analyzing and discussing intelligent decision support systems such as neural network systems and technologies, fuzzy logic systems, genetic algorithms, and systems the expert. Study objectives: The main objective of this study is to try to identify and study the applications of artificial intelligence in support of administrative decisions, by achieving the following objectives, defining the concept of the field of artificial intelligence, and the relative importance of each of its components that it includes; Determine the modus operandi of the most prominent known applications of artificial intelligence in solving problems; Define the architecture and structure of AI applications (neural network systems and technologies, fuzzy logic systems, genetic algorithms, and expert systems); Determine the benefits offered by artificial intelligence applications when used. Study structure: Based on the study problem, its objectives, and its importance, the elements of the study can be identified as follows: The first topic: Analyzing the concept of artificial intelligence; the second topic: studying the applications of artificial intelligence in support of administrative decisions in business organizations and e-government. The Approach: The inductive approach was used, through extrapolation and analysis of studies, research, books, and periodicals related to the field of study, to identify the theoretical basis for applications of artificial intelligence in support of administrative decisions in business organizations and e-government